Profil Anatomi Batang Kacang Komak (Lablab purpureus (L.) Sweet) Lokal Pulau Lombok - Ervina Titi Jayanti (Biota, 2017)
Hyacinth bean (Lablab purpureus (L.) Sweet) is a member of Fabaceae which has high economic potential but is still treated as an underutilized crop. Research on Lombok’s hyacinth bean focused on stem anatomical profile has never been conducted. The aims of this research were to study stem anatomical profile of hyacinth bean in Lombok, West Nusa Tenggara. Young and mature stem were collected using exploration method. Anatomical sample preparation was done using free hand section method, stained with safranin, and mounted in a glycerine liquid. Sample was visualized and documented using binocular microscope connected to the digital camera integrated with ScopeImage 9 software. Data were analyzed by a triangulation method. The result showed that stem anatomical profile of hyacinth bean in Lombok by transversal section consists of one layer of an epidermal cell and unicellular glandular trichomes as it’s derivate. Parenchyma cell was found in the cortex, interfascicular region, and pith in shape of rounded, oval, up to polygonal and varied in size. Vascular tissue showed a unique structure and became the distinctive feature od hyacinth bean stem. There were 2 type of vascular bundles i.e big and small vascular bundles. The large vascular bundles contain xylem and phloem and the small vascular bundles may or may not contain both xylem and phloem.